Arthritis and Osteomyelitis due to Aspergillus fumigatus: A 17 years old boy with chronic granulomatous disease - Tabak Yalcın; Balaban Neriman; Colpan Aylin; Ozoran Kursat; Bodur Hurrem; Kulacoglu Sezer (BMC, 2003)
Abstract Background Invasive Aspergillus infections are frequently seen in immunocompromised patients but arthritis is a rare complication of Aspergillus infections in the absence of immune suppressive therapy, trauma or surgical intervention. Case presentation A 17 years old male patient with arthritis and patellar osteomyelitis of the left knee whose further investigations revealed chronic granulomatous disease as the underlying disease is followed. Aspergillus fumigatus was isolated from the synovial fluid and the tissue samples cultures. He was treated with Amphotericin B deoxicolate 0.7 mg/kg/day. Also surgical debridement was performed our patient. Amphotericin B nephrotoxicity developed and the therapy switched to itraconazole 400 mg/day. Itraconazole therapy were discontinued at the 6th month. He can perform all the activities of daily living including. Conclusion We think that, chronic granulomatous disease should be investigated in patients who have aspergillar arthritis and osteomyelitis.